Correlation between psychological factors and the expression of galanin and 5.hydroxytryptamine in different subtypes of gastroesophageal reflux disease - Yuan Yuan; Hui-Wen Xu; Song Zhang; En Takashi; Kitayama Akio; Jing-Yan Liang (Wolters Kluwer Medknow Publications, 2021)
Objective: The aim of this study is to analyze the differences in galanin (GAL) and 5-hydroxytryptamine (5-HT) levels in patients with different subtypes of gastroesophageal reflux disease (GERD) and its correlation with anxiety and depression in patients. Methods: Using the reflux disease questionnaire, 238 patients with GERD were selected as the study group. According to the endoscopic performance, they were divided into the nonerosive reflux disease (NERD) group (114 patients) and the RE group (124 patients). Sixty healthy people were selected as the control group. All research subjects were tested using the self-rating anxiety scale (SAS) and the self-rating depression scale (SDS) to assess the severity of anxiety and depression. The levels of 5-HT and GAL were analyzed using enzyme-linked immunosorbent assay. Results: Compared with the control group, 5-HT level in GERD patients without anxiety and depression was higher (t = 1.97, P < 0.05) and GAL level was lower (t = 1.97, P < 0.05). NERD patients demonstrated more server anxiety (F = 55.92, P < 0.05) and depression problems (F = 36.51, P < 0.05) compared to reflux esophagitis (RE) patients. The 5-HT level was lower (F = 54.53, P < 0.05) and the GAL level was higher (F = 8.00, P < 0.05) in NERD patients compared with the control group. Furthermore, 5-HT level was negatively correlated with SAS (r = −0.789, P < 0.05) and SDS (r = −0.787, P < 0.05) scores; GAL level was positively correlated with SAS (r = 0.688, P < 0.05) and SDS (r = 0.705, P < 0.05) scores; 5-HT and GAL level were negatively correlated (r= −0.744, P < 0.05). Conclusions: 5-HT level is higher and GAL level was lower in GERD patients without anxiety and depression than healthy people; the symptoms of anxiety and depression of NERD patients are more severe compared to those of RE patients; the severity of anxiety and depression was negatively correlated with the level of 5-HT and positively with GAL level.